Intratracheal Administration of Budesonide-instilled Surfactant for Prevention of Bronchopulmonary Dysplasia: A Randomized Controlled Clinical Trial - Amir Mohamad Armanian; Ramin Iranpour; Asghar Lotfi; Raziyeh Amini; Negin Ghasemi Kahrizsangi; Afrooz Jamshad; Parastoo Shiranilapari; Awat Feizi (Mashhad University of Medical Sciences, 2023)
Background: Despite numerous clinical strategies performed over the years, Bronchopulmonary dysplasia (BPD) still remains a common disease with considerable long-term adverse effects in very premature infants. This study investigated the effect of budesonide-instilled surfactant on the incidence of BPD in preterm infants.Methods: In this clinical trial, a total of 190 neonates with a gestational age of less than 30 weeks, who were identified as candidates for surfactant therapy, were randomly assigned to two groups. The control group (S) received surfactant at a dosage of 200 mg/kg for the initial dose and 100 mg/kg for subsequent doses. In cases where it was deemed necessary (n=95), the intervention group (BS) received surfactant along with budesonide, instilled once at a dose of 0.25 mg/kg (n=95). The primary outcome was the occurrence of BPD, and the combined incidence of BPD and death Secondary outcomes encompassed other complications related to prematurity and adverse effects associated with corticosteroid use.Results: Demographic characteristics of the neonates were comparable between the two groups.  Although a slight reduction was seen in the incidence of BPD in the group receiving budesonide, BPD rates remained statistically unchanged after the intervention (48.4% in the BS group vs 50.5% in the S group, P value = 0.772). The combined outcome of BPD and death was insignificantly different between the two groups (61.1% in the BS group vs. 63.2% in the S group, P value = 0.765). The addition of budesonide resulted in an increased incidence of sepsis and pneumothorax in the control group. However, secondary outcomes such as IVH (Inra ventricular Hemorrhage(, retinopathy of prematurity, necrotizing enterocolitis, patent ductus arteriosus, and hyperglycemia were unaffected. Duration of total parenteral nutrition and hospitalization time were longer in the BS group than in the S group.Conclusion: The addition of budesonide to surfactant in very premature neonates at gestational age <30 weeks who were candidates for surfactant therapy did not prevent BPD. Conversely, it led to an increase in certain secondary morbidities such as sepsis and pneumothorax. Furthermore, it extended the duration of hospitalization.